Thematic review of factors that contribute to family well-being during movement control order (mco) - Saidon, Rafeah; Ab Manan, Siti Khadijah; Hamjah, Salasiah Hanin; Jaapar, Nurzahidah; Zainudin, Ulfah Mansurah (Penerbit UiTM, 2022)
Family well-being is critically essential in shaping a sustainable healthy society and nation. This is important when the nation is struck with disasters such as the pandemic covid 19. Family units must be strong in facing the adverse effects of the pandemic. Preserving family well-being is consistent with the 11th Malaysia Plan (RMK 11) which sets one of its targets to improve the well-being of society. Therefore, the goal of this thematic review is to synthesize literature from 2020-2022 on the family well-being during COVID-19 using ATLAS.ti 8. A keyword search, followed by a filter using inclusion criteria from SCOPUS, WoS, and Mendeley databases, identified 50 peer-reviewed journal articles. However, after the inclusion and exclusion process, only 39 articles were used as the final articles to be reviewed. A thematic review of these articles identified 63 initial codes characterizing family well-being during pandemic COVID-19, grouped into 5 clusters: 1) spiritual and psychological needs 2) building resilience during COVID-19 3) negotiation 4) motivation and 5) emotional well-being. The results may benefit future studies on family well-being during pandemics and can be a guideline for developing family happiness.